Entomological Investigations, Seasonal Fluctuations and Impact of Bioclimate Factors of Phlebotomines Sand Flies (Diptera: Psychodidae) of an Emerging Focus of Cutaneous Leishmaniasis in Aichoun, Central Morocco. (7th July 2020) - Talbi, Fatima Zahra; El Ouali Lalami, Abdelhakim; Fadil, Mouhcine; Najy, Mohamed; Ech-Chafay, Hassan; Lachhab, Mohamed; Lotfi, Said; Nouayti, Nordine; Lahouiti, Khadija; Faraj, Chafika; Janati Idrissi, Abdellatif
Abstract : Leishmaniasis diseases are endemic in Morocco. An entomological survey was conducted in Aichoun locality for 1 year from September 2013 to August 2014. The objective of this study was to investigate the sand fly fauna, mainly the species composition and the monthly species prevalence in accordance with bioclimate factors. Sand flies were collected twice a month, using sticky traps and CDC light traps. During a one-year study, 4472 specimens of sand fly were caught (72.56% male/22.44% female) that were composed of seven species divided into two genera: Phlebotomus (99.46%) and Sergentomyia (0.53%). Ph. sergenti was the most prevalent species (46.64%), followed by Ph. perniciosus (38.19%), Ph. longicuspis (9.32%), Ph. papatasi (5.23%), and Ph. ariasi (0.06%). The genus Sergentomyia was even less frequent. The population dynamics showed a bimodal trend with two peaks: the first one in October (12.03% of specimens) and the second in June (27.92% of specimens). The study of the effects of climatic factors in the study area showed a link between the dynamics of sand flies and the variation of these parameters (temperature and relative humidity). During the period between November and March, the sand flies were absent. The highest prevalence of sand flies was recorded in June when the temperature and relative humidity values reached, respectively, 25.8°C and 42%. The minimum number of specimens was collected in September with an average temperature of 23.19°C and relative humidity of 57.4%. Statistical analysis with principal component analysis has shown a strong positive correlation between temperature parameters and the seasonal distribution of sand flies. The climatic factor of relative humidity has been judged of being negatively correlated. The wind speed does not have any impact on the relative abundance of all species. Within this context, the results will be useful for the development of a monitoring program to better manage the operations and evaluate their effectiveness.